Keadilan Gender dalam Tafsir Ayat Suci Lenyepaneun: Kajian Pendidikan Berbasis Ma’na-Cum-Maghza atas QS 4: 124, 16: 97, dan 40: 40 - Elis Tuti Winaningsih (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study examines the values ​​of gender-equitable education in Muhammad Emon Hasim's Tafsir Ayat Suci Lenyepaneun using the Ma'na-Cum-Maghza theory. This study is motivated by the continued dominance of gender bias in the interpretation of the Qur'an and the limited study of local Nusantara interpretations. This study aims to analyze the interpretation of QS 4:124, QS 16:97, and QS 40:40 and identify the values ​​of gender-equitable education they contain. This research is a qualitative literature study with a contextual interpretation and gender analysis approach. The primary data is the Tafsir Ayat Suci Lenyepaneun, while secondary data comes from classical and modern interpretations, and Islamic gender literature. The analysis is carried out through the stages of ma'na (historical-linguistic meaning) and maghza (ideal and contextual significance). The results of this study indicate that the interpretation of the Lenyepaneun Holy Verse affirms the equality of men and women in faith, deeds, and rewards, and contains educational values ​​of faith, morals, and gender-just practices. The novelty of this research lies in its exploration of the integration of Sundanese culture into gender interpretation, which makes a significant contribution to the study of Indonesian interpretation.